THE EFFECTIVENESS OF DIGITAL MONOLOGUE LEARNING MODEL IN ENHANCING ACTING EXPRESSION AND INNER ACTING SKILLS AMONG DRAMA EDUCATION STUDENTS - Welly Suryandoko; Autar Abdillah; Syaiful Qadar Basri (Nurul Jadid University, 2025)
The rapid advancement of digital technology has transformed drama education, particularly acting instruction delivered through online platforms. However, limited research has examined the effectiveness of digital learning in improving students' expressive abilities and inner acting. This study evaluates the effectiveness of the Digital Monologue learning model as an e-learning strategy for enhancing expression and inner acting among undergraduate drama education students. A quasi-experimental design was employed involving four classes in the Drama, Dance, and Music Education program at Surabaya State University. Two classes served as the experimental group, while two acted as the control group. Data were collected through performance assessments measuring expression and inner acting and analyzed using normalized gain (N-Gain) and paired-sample t-tests. The findings revealed that the experimental group achieved moderate N-Gain scores (0.42–0.43), outperforming the control group (0.20–0.28). Paired-sample t-test results indicated significant improvements between pre-test and post-test scores (p < 0.05). These findings demonstrate that the Digital Monologue learning model effectively enhances acting performance and provides an innovative digital framework for preserving artistic quality while supporting online drama education.